A comparison of balance control between javelin throwers and baseball pitchers - Lin, W.-H.; Cheng, J.-H.; Hung, W.-H.; Lee, A. J. Y. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This study evaluated the balance control in javelin throwers and baseball pitchers. Twenty-four athletes took part in the study and for each we measured their static and dynamic balance by Biodex Balance System, AMTl AccuSway force plate and Y balance test. The paired t-test was conducted to compare all the variables within subjects. The independent t-test was used to compare trail leg (TL) of baseball pitchers with propulsive leg (PL) of javelin throwers and stride leg (SL) of baseball pitchers with braking leg (BL) of javelin throwers. The results showed that there was no difference between the PL and BL in dynamic and static balance in javelin throwers. However, the dynamic balance in the TL was significantly better than the SL in baseball pitchers. The static balance in the PL in javelin throwers was also better than the TL in baseball pitchers. The research improves the understanding of balance control in elite athletes.